How Artificial Intelligence Can Affect Product Costing: A Look Into the Interaction Between Duration-Based Costing and Artificial Intelligence - Lelkes, Anne-Marie Teresa (Journal of Accounting and Finance, 2024)
There has been much discussion regarding integrating Artificial Intelligence (AI) into accounting. This study focuses on the integration of AI with product costing models, most specifically with the Duration-Based Costing (DBC) model. The published literature regarding DBC shows that DBC can mimic or outperform an Activity-Based Costing (ABC) model that utilizes time drivers. Furthermore, the large amount of information that an ABC system utilizes can cause information overload, which DBC overcomes. DBC is a cost allocation technique that assigns overhead costs based on the production cycle time. The more time that a company spends producing a product, the more it will cost. DBC utilizes the concept “time is money.” DBC is the model that looks at the larger picture. In other words, DBC looks at the forest overall whereas ABC looks at each individual tree in which the saying “cannot see the forest for the trees” applies to ABC. Therefore, this study aims to discuss how AI can integrate with DBC to provide a company valuable and quick cost information.